Phylogenetic analysis of the South American sharpshooter genus Scopogonalia Young, 1977 (Insecta: Hemiptera: Cicadellidae), with implications for conservation - Leal, Afonso H.; Creão-Duarte, Antonio J.; Mejdalani, Gabriel (Zootaxa, 2020)
Scopogonalia is a leafhopper genus with 17 described species, all of them from South America. In this work, a phylogenetic analysis of the genus was conducted based on 59 morphological and colour pattern characters of head, thorax, abdomen, male and female genitalia. Analyses with equal weights resulted in 12 equally most parsimonious trees (length = 137) including a monophyletic Scopogonalia in all of them. An implied weights (k = 15) analysis recovered two trees, one of them equal to the one obtained with a single round successive weighting procedure, which was chosen for discussion. The trees support the existence of three main clades, which are here called Early Green Clade, Late Green Clade, and Yellow-Brown Clade. The origin and diversification of each clade is discussed under available biogeographical knowledge of South America. Little variation was observed in the female genitalia, but their characters were useful to reinforce the monophyly of the Yellow-Brown Clade, which we associate to ecological adaptations. This clade supports a past connection of the Cerrado biome and savannah enclaves in Amazonia and Atlantic Forest. This conclusion highlights the necessity of conserving this open vegetation environment inside the most fragmented portion of the Atlantic Forest, in northeastern Brazil.